A Tobit Analysis of the Determinants and Potentials of Savings in the Case of Payatas Households - Chua, Nina Ellorah A.; Kiong, Shaira Kasey L.; Villa, Kristine Honey M.; Paguta, Ronald B. (Information Management and Business Review, 2016)
This case study aims to identify the factors affecting household savings in the Area B of Payatas, Quezon City. Particularly, the variables included in the analysis are economic expectations, homeownership, household consumption, household debt, household disposable income, and number of dependents in the household. This paper also aims to analyze the saving potentials of households in Payatas. A total of 422 conditionally and randomly selected households were interviewed through a guided survey questionnaire. The researchers utilized Tobit regression and computed for the conditional marginal effects for both the censored and truncated sample. The results of the study were divided into three: Tobit regression results, conditional marginal effects results on all respondents, and the conditional marginal effects results on household savers. Significant variables such as economic expectations and household disposable income were found to be positively related to household savings, and household consumption was negatively related to household savings. This case study shows that Payatas B households do have saving potentials irrespective of their low income showing high request for accessibility on formal saving institutions.